Digital Resilience in the Age of AI: The Role of Media and Information Literacy (MIL) in Empowering Gen Z and Enhancing ESG Outcomes - Grumadaitė, Kristina; Babu, Sebin Thomas (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
A coherence between media and information literacy (MIL), digital resilience, empowerment of Gen Z, and Environmental Social Governance (ESG) could be seen as a complex contemporary phenomenon in the context of the development of Artificial Intelligence (AI), when MIL acts a structural mechanism, which enables Gen Z to become digitally resilient and influence ESG outcomes accordingly. Empirical research on MIL in Lithuanian Gen Z individuals aged 16-19 and 20-24 revealed a moderate level of MIL, which further increases in the group of 20-24 years old. However, research results revealed that the respondents tend to be less reactive and thus take no proactive efforts, particularly in analysing the digital content from different perspectives or warning others regarding fake news. Recognising the identified gaps in MIL, the study proposes comprehensive solutions through the implementation of ESG-aligned practices aimed at strengthening digital resilience among Gen Z.